Molecular and Cellular Mechanisms Associated with Effects of Molecular Hydrogen in Cardiovascular and Central Nervous Systems - Miroslav Barancik; Branislav Kura; Tyler W. LeBaron; Roberto Bolli; Jozef Buday; Jan Slezak (MDPI AG, 2020)
The increased production of reactive oxygen species and oxidative stress are important factors contributing to the development of diseases of the cardiovascular and central nervous systems. Molecular hydrogen is recognized as an emerging therapeutic, and its positive effects in the treatment of pathologies have been documented in both experimental and clinical studies. The therapeutic potential of hydrogen is attributed to several major molecular mechanisms. This review focuses on the effects of hydrogen on the cardiovascular and central nervous systems, and summarizes current knowledge about its actions, including the regulation of redox and intracellular signaling, alterations in gene expressions, and modulation of cellular responses (e.g., autophagy, apoptosis, and tissue remodeling). We summarize the functions of hydrogen as a regulator of nuclear factor erythroid 2-related factor 2 (Nrf2)-mediated redox signaling and the association of hydrogen with mitochondria as an important target of its therapeutic action. The antioxidant functions of hydrogen are closely associated with protein kinase signaling pathways, and we discuss possible roles of the phosphoinositide 3-kinase/protein kinase B (PI3K/Akt) and Wnt/β-catenin pathways, which are mediated through glycogen synthase kinase 3β and its involvement in the regulation of cellular apoptosis. Additionally, current knowledge about the role of molecular hydrogen in the modulation of autophagy and matrix metalloproteinases-mediated tissue remodeling, which are other responses to cellular stress, is summarized in this review.